Modelling of Dewatering and Desalting Processes for Large-capacity Oil Treatment Technology; Procedia Chemistry; Vol. 10 : Chemistry and Chemical Engineering in XXI century - Kim S. F.; Usheva N. W. Natalia Wladimirowna; Moyzes O. E. Olga Efimovna; Kuzmenko E. A. Elena Anatolievna; Samborskaya M. A. Marina Anatolievna; Novoseltseva E. A. (2014, 2014)
Title screen